PBA4 Philippine banking almanac 4 - Litiatco, Vicki J. (Manila Ventures Unlimited, 2000)
Has 2 parts - part 1 focuses on issues in the banking industry, and part 2 is a list of supervisory and regulatory agencies, specialized government banks, expanded commercial banks- domestic, domestic commercial banks, private foreign commercial banks, savings and mortgage banks, private development banks, stock savings and loan associations, rural banks, offshore banking units, representative offices of foreign bank associations and ATM organizations. Each bank /org/office/association is presented with information on their typology, principal address, contacts, members, branches, ownership, auditor, historical highlights, board of directors, officers, financial highlights, products and services, and affiliates and subsidiaries. The almanac also features the Republic Act no. 8791 an act providing for the regulation of the organization and operation of banks, quasi- banks, trust entities, and for other purposes.
Keywords: Banks and banking -- Philippines; Banks and banking -- Philippines -- Directories; Banks and banking -- History. -- Philippines; Financial institutions -- Philippines